Potentiometric Determination of Some Strong Oxidants Using Fluoride Ion-Selective Electrode - KARIMI, M.A.; MAZLOUM ARDAKANI, M.; TADAYON, M. (Asian Journal of Chemistry, 2010)
A new, simple, inexpensive and sensitive method for the microdetermination of strong oxidants of hydrogen peroxide (H2O2), peroxyacetic acid (PAA), permanganate (MnO4–), dichromate (Cr2O72-), chromate (CrO42-) and cerium(IV) has been investigated and developed. In this work, the oxidation reaction of Fe(II) to Fe(III) in the presence of oxidants is based on the method. The change potential of complexation of flouride ion with Fe(III) was monitored by a fluoride ion-selective electrode. A series of experiments were conducted to establish the optimum analytical parameters to achieve maximum sensitivity in the determination of above oxidants. The experimental parameters such as ionic fluoride and iron(II) concentrations, temperature and pH of solutions were optimized. The results showed that determination of H2O2, peroxyacetic acid, MnO4–, Cr2O72-, CrO42- and Ce(IV) could be performed in their concentration ranges of 1.0-1.0, 0.1-10.0, 0.1-10.0, 0.1-20.0 and 0.5-20.0 μg mL-1, respectively. The proposed method was successfully applied to the determination of strong oxidants in synthetic water samples.